Applications of polymers in drug delivery - Misra, Ambikanandan; Shahiwala, Aliasgar (Smithers Rapra, 2014)
Use of polymers has become indispensable in the field of drug delivery. Polymers play a crucial role in modulating drug delivery to exploit maximum therapeutic benefits and have been fundamental in the successful development of several novel drug delivery systems that are now available. This book provides details of the applications of polymeric drug delivery systems that will be of interest to researchers in industries and academia. It describes the development of polymeric systems ranging from the conventional dosage forms up to the most recent smart systems. The regulatory and intellectual.
Keywords: Polymeric drug delivery systems.; Drug delivery systems.; Polymers.; elektronické knihy; electronic books